Rituximab-mediated late-onset neutropenia in systemic lupus erythematosus – distinct roles of BAFF and APRIL. (August 2018) - Parodis, I; Söder, F; Faustini, F; Kasza, Z; Samuelsson, I; Zickert, A; Svenungsson, E; van Vollenhoven, R F; Malmström, V; Wermeling, F; Gunnarsson, I
Objective: Rituximab-mediated late-onset neutropenia (LON) has been described in various diseases. We investigated its occurrence, consequences and contributing factors in patients with systemic lupus erythematosus (SLE). Methods: Rituximab-treated patients from the Karolinska University Hospital ( n = 107) were surveyed. LON was defined as an absolute neutrophil count <1500 cells/μl, occurring four weeks to two years following rituximab treatment, or later during sustained B-cell depletion. Serum levels of B-cell-related cytokines and growth factors of the myeloid lineage were determined using enzyme-linked immunosorbent assay. Results: Thirty-two patients (29.9%) developed LON after a median time of 201.5 days. Thirteen patients were admitted to the hospital; 10 due to fever. Three patients developed critical conditions. BAFF levels increased from baseline (median: 0.62 ng/ml) to the post-treatment evaluation (median: 1.16 ng/ml; p < 0.001); post-treatment levels were higher in the LON group ( p = 0.021). APRIL levels were higher in the LON group both at baseline (median: 1.54 versus 1.15 ng/ml; p = 0.027) and post-treatment (median: 2.39 versus 1.11 ng/ml; p = 0.011). IL-6 and GM-CSF levels decreased in the non-LON group ( p < 0.001), but not in LON patients. High baseline disease activity predicted LON development (OR: 4.1; 95% CI: 1.1–15.2 for SLEDAI-2K > 8). No association with neutropenia prior to rituximab treatment was documented. Conclusion: Post-rituximab LON was a common complication. Although the phenomenon was predominantly self-limiting, several patients developed severe conditions. Distinct roles of BAFF and APRIL are implicated: BAFF may contribute to LON development, whereas high APRIL levels may be predictive. Rituximab-treated SLE patients should be monitored for neutrophil counts, fever and infections.